Peningkatan Produktivitas UMKM Menggunakan Metode American Productivity Center - Hadi, Yuswono; Irawan, Roy; Kelana, Oesman Hendra (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2018)
Growth and development of SMEs in Indonesia is the responsibility of all parties. This research was conducted as an effort to increase the productivity of micro enterprises Tempe manufacturer in Pasuruan, East Java. The method used is the American Productivity Center. The advantage of this method is to produce three measures of productivity, the index of productivity, profitability index and the index of price improvement. After the measurement, analysis and improvement efforts showed the proposed implementation of the improvements made in the period May managed to increase the productivity index and the index of profitability compared with the period before the implementation of the April. Input materials, labor, energy and total input increased by (6.21%); (3.67%); (8.60%) and (0.0385%), while capital decreased by (-6.34%). The profitability index of material inputs, labor, energy and total input increased by (7.54%) (3.52%), (8.26) and (0.04), while capital input declined by (-8 , 67%). Price improvement index showed a decrease in labor input of energy and capital by (0.02%) (0.02%) and (2.08%). Material inputs increased by (1.55%), while the total input unchanged.